Sex, Crimes and Secrets: Invention and Imbroglio in Recent Brontë Biographical Fiction. (November 2014) - Stoneman, Patsy
<x content-type="archive" xml:space="preserve">Abstract</x> The last twenty years have seen a proliferation of fictional works which supplement, rewrite or allude to Brontë biography, augmenting the known facts with more or less plausible invention. Noting that recent literary theories have destabilized the distinction between 'fact' and 'fiction', I consider two categories of such fiction: those based on a biographical hypothesis, and those in which present-day readers are 'haunted' by the Brontë lives. Many of these stories turn on the discovery of documents, and I shall argue that the best of them offer hypotheses which address the aporias — the gaps and puzzles — in scholarly biography.